1970
DOI: 10.1159/000192734
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Recurrent Bronchitis in Childhood

Abstract: This paper reports the findings of a study which has been carried out in a general practice for the past 18 months, its principal aims being to investigate the causes of acute lower respiratory disease (= LRD) in children and to investigate constitutional factors which may predispose to recurrent episodes of LRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1972
1972
1980
1980

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…An association between infection by rhinoviruses and acute episodes of bronchitis and asthma has been reported by other workers, both in adults (Eadie et al 1966;Stenhouse 1967;Lambert & Stern 1972;Gregg 1975;Minor et al 1976) and in children (Gregg 1970;Minor et al 1974a, c;Mitchell et al 1978;Horn et al 1979).…”
Section: Discussionmentioning
confidence: 54%
“…An association between infection by rhinoviruses and acute episodes of bronchitis and asthma has been reported by other workers, both in adults (Eadie et al 1966;Stenhouse 1967;Lambert & Stern 1972;Gregg 1975;Minor et al 1976) and in children (Gregg 1970;Minor et al 1974a, c;Mitchell et al 1978;Horn et al 1979).…”
Section: Discussionmentioning
confidence: 54%
“…Breast feeding has been thought to influence the incidence of 'allergic disease'. Grulee & Sanford, 1936 found that breast fed infants were less likely to develop eczema. In a personal 20-year follow up of children seen from 1948 to 1952, the incidence of eczema was two and a half times less in the breast fed infant (Blair, 1969).…”
Section: Discussionmentioning
confidence: 98%
“…In a survey of all forms of acute respiratory illness in children, aged 0-12 years, in a London general practice (Gregg, 1970(Gregg, , 1975Horn et al, 1975), one of our principal aims was to elucidate the role of viral infection in wheezy bronchitis. We have used this term to denote episodes of illness whose salient features are cough and the presence on auscultation of wheeze in addition to crackles.…”
mentioning
confidence: 99%